Ultrastructural studies of the mandibular gland of Melipona quadrifasciata Lepeletier, 1836 (Apidae, Meliponini): a comparison between workers and queens - da Cruz-Landim, Carminda [UNESP]; Gracioli-Vitti, Luciana Fioretti [UNESP]; Abdalla, Fábio Camargo [UNESP] (Int Bee Research Assoc, 2011)
The mandibular glands of workers and queens of Melipona quadrifasciata Lepeletier 1836 were studied in different functional states under transmission electron and light microscopy. In both castes, the glands consisted of a cluster of class III secretory cells and a small, thin-walled reservoir. The glands of queens were smaller than those of workers. The gland of workers were more developed in nurses, in which they consisted of secretory cells rich in smooth endoplasmic reticulum and lipid-like secretion. Among workers, the stored secretion seemed to be used only by foragers. In queens, the gland is more active in virgin than in physogastric queens, being the secretion likely composed mostly of proteins. Our results suggest that the secretion is mainly useful for foragers and virgin queens. Secretion appears to play a role in pheromone activity.
Keywords: exocrine glands; Melipona quadrifasciata; Meliponini; morphology; histology; mandibular gland; stingless bee; ultrastructure